Spatial and temporal trends of alternative flame retardants and polybrominated diphenyl ethers in ringed seals (Phoca hispida) across the Canadian Arctic. (April 2017) - Houde, M.; Wang, X.; Ferguson, S.H.; Gagnon, P.; Brown, T.M.; Tanabe, S.; Kunito, T.; Kwan, M.; Muir, D.C.G.
Abstract: Concentrations of alternative flame retardants and polybrominated diphenyl ethers (PBDEs) were analyzed in ringed seal ( Phoca hispida ) blubber collected across the Canadian Arctic during subsistence hunts between 1998 and 2013. More than 80% of sampled animals were females and juvenile males. The highest mean ΣPBDE concentrations (sum of 13 congeners) were found in seals from Nain (Nunatsiavut) as well as Inukjuaq and Arviat (Hudson Bay) and the lowest mean levels were found in seals from Lancaster Sound. BDE-47 and -99 were the predominant PBDE congeners quantified in ringed seals. The most frequently detected non-PBDE flame retardants were polybrominated biphenyl 101 (BB-101, 57% of samples analyzed for this chemical), hexabromocyclododecane (HBCDD; 38%), hexabromobenzene (HBB, 30%), and 2-ethylhexyl-2, 3, 4, 5-tetrabromobenzoate (EHTeBB, 23%). The relative trophic position of seals, estimated using stable isotopes, did not vary over time and did not influence flame retardant blubber concentrations. The relative carbon source increased over time at Arviat and Resolute Bay and weak relationships were observed with ΣPBDEs in blubber of seals. ΣPBDEs increased significantly from 1998 to 2008 in ringed seals from East Baffin and subsequently decreased in recent years. PBDE levels at other sites fluctuated slightly over time. HBCDD concentrations increased at several sites over the past decade. The presence of flame retardants in ringed seals suggests their persistence and their continuous inputs in the Canadian Arctic environment. Monitoring and research on the effects of these contaminants in seals are warranted given the importance of this species in Arctic marine food webs and for local communities. Graphical abstract: Highlights: Alternative flame retardants and PBDEs were analyzed in Canadian Arctic ringed seal blubber (1998–2013). Highest PBDE concentrations were found in Hudson Bay and Nain, the southernmost sampling sites. BB-101, HBB, HBCDD, and EHTeBB were the predominant non-PBDE flame retardants detected in blubber. ΣPBDEs increased (1998–2008) in East Baffin seals and decreased in recent years (2008–2011). HBCDD concentrations increased at several sites over the past decade. Abstract : Alternative flame retardants and PBDEs were investigated in ringed seals across the Canadian Arctic.